Pemutusan Hubungan Kerja Sepihak Dan Upah Dibawah UMK Kota Surabaya Yang Dilakukan Oleh PT HSM - Nashiwa Laili Novrina; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In writing this journal, it aims to find out that in Indonesia there are still many workers who cannot fulfill the rights that workers should get. One of them is in Surabaya City, which was carried out by PT HSM by unilaterally terminating employment (PHK) and the wages earned by workers below the Surabaya City Minimum Wage. In the termination of employment, PT HSM did not fulfill the rights that should be obtained by workers such as compensation and compensation. Termination of employment and wages are the most important things for workers. If workers experience unilateral layoffs and receive inappropriate wages, it will have an impact on the economic stability of workers in meeting the needs of themselves and their families. Therefore, there are regulations governing employment and the rights that must be obtained by workers.